Cell-free supernatants from cultures of lactic acid bacteria isolated from fermented grape as biocontrol against Salmonella Typhi and Salmonella Typhimurium virulence via autoinducer-2 and biofilm interference - Wattana Pelyuntha (2020)
© 2019 Pelyuntha et al. Background. Salmonella Typhi and Salmonella Typhimurium are the causative pathogens of salmonellosis, and they are mostly found in animal source foods (ASF). The inappropriate use of antibiotics enhances the possibility for the emergence of antibiotic resistance in pathogens and antibiotic residue in ASF. One promising alternative to antibiotics in animal farming is the use of lactic acid bacteria (LAB). Methods. The present study was carried out the cells and/or the cell-free culture supernatants (CFCS) from beneficial LAB against S. Typhi and S. Typhimurium. The antibacterial mechanisms of LAB-CFCS as biocontrol agents against both Salmonella serovars were investigated through the analysis of anti-salmonella growth activity, biofilm inhibition and quorum quenching activity. Results. Among 146 LAB strains isolated from 110 fermented food samples, the 2 strong inhibitory effect strains (WM33 and WM36) from fermented grapes against both Salmonella serovars were selected. Out of the selected strains, WM36 was the most effective inhibitor, which indicated S. Typhi by showing 95.68% biofilm inhibition at 20% biofilm inhibition concentration (BIC) and reduced 99.84% of AI-2 signaling interference. The WM33 was the best to control S. Typhimurium by producing 66.46% biofilm inhibition at only 15% BIC and 99.99% AI-2 signaling a reduction. The 16S rDNA was amplified by a polymerase chain reaction (PCR). The selected isolates were identified as Weissella viridescens WM33 and Weissella confusa WM36 based on nucleotide homology and phylogenetic analysis. Conclusion. The metabolic extracts from Weissella spp. inhibit Salmonella serovars with the potential to be used as biocontrol agents to improve microbiological safety in the production of ASF.